(untitled) (NUML International Journal of Business & Management, 2022)
To investigate “Twin Deficit Challenge: An Evidence from Pakistan Economy” this study employed SAM 2010-11 for Pakistan (Dorosh, Niazi, and Nazli, 2015). This study used a static CGE model. The theoretical structure of the core model closely follows the Lofgren et al. (2001) model, with an extension to incorporate commonly observed specifications of a developing country (Naqvi 2011). The study concludes that the lag value of budget deficit and trade deficit are the main factors contributing to the twin deficit. Two experiments were conducted to check the effects. The experiments were conducted on Direct and Indirect tax to remove internal deficit in the economy. The study explored that the internal resources play a vital role in removing the twin deficit gap. The objective of this experiment was to determine the possibility of implementation of direct and indirect tax in the case of Pakistan and to analyze its benefits at the macro and household levels. The findings of the study recommend that budget deficits possess threats to fiscal policy. Results show that a policy mix of sales tax, income tax and government expenditure help to reduce income inequality while it reduces the financial dependency of the economy. Therefore, Pakistan should strive to reduce the budget deficit using a mix of macroeconomic policies.